Generic machining process sequencing through a revised enriched machining feature concept. (October 2015) - Givehchi, Mohammad; Haghighi, Azadeh; Wang, Lihui
Abstract: Nowadays, small and medium-sized enterprises (SMEs) require a highly competitive process planning approach in order to survive. This mainly is due to the abrupt and continuous changes that occur every day in the production plant. This paper proposes a generic process sequencing approach that due to its independency to available resources can increase adaptability and flexibility of the system. The proposed method can be used by the Cloud-DPP (distributed process planning) in an integrated cyber-physical system. This rule-based approach requires the definition of a new revised enriched machining feature concept. The proposed concept not only possesses information of the machining feature itself (geometrical information, tolerances and coordinates system), but also contains additional information that are discussed in detail throughout the paper. A data format has been defined for the introduced additional data and the machinability rule has been defined as the key rule for sequencing. The sequencing approach in this work applies four sets of rules but can be extended if new rules are needed. The proposed method is then validated through a case study.